Equilibrium, Thermodynamics, and Kinetic Sorption Studies for the Removal of Coomassie Brilliant Blue on Wheat Bran as a Low-Cost Adsorbent. (27th March 2012) - Ata, Sadia; Imran Din, Muhammad; Rasool, Atta; Qasim, Imran; Ul Mohsin, Ijaz
Abstract : The sorption studies of coomassie brilliant blue (CBB) from aqueous solution have been carried out on wheat bran (WB). Coomassie brilliant blue on wheat bran was used to study the adsorption behavior under various parameters such as pH, dosage amount, and contact time. It was observed that under optimized conditions up to 95.70% dye could be removed from solution onto WB. Langmuir and Freundlich adsorption isotherms were used to elaborate the results. Freundlich model was found to be fitted well and favored multilayer adsorption. The Freundlich constants n and KF were determined as 0.53 and 2.5 × 10 − 4 . Thermodynamic parameters such as Δ G, Δ H, and Δ S studied were taking into account, showed spontaneous and favorable reaction for coomassie brilliant blue on wheat bran. The maximum adsorption capacity q m was found to be 6.410 mg/g. The investigations show that non treated WB is a low-cost adsorbent for the removal of dyes from textile industry effluents.